Polycyclic aromatic hydrocarbons in water, sediment and fish from the Warri River at Ubeji, Niger Delta, Nigeria (2015)
The Warri River at Ubeji, Nigeria, receives pollutants from an oil refinery. The levels of 16 priority polycyclic aromatic hydrocarbons (PAHs) in water, sediment and the tissue of tilapia from the Warri River were investigated in 2010 using gas chromatography with mass spectrometry. Eleven PAHs were found in the sediment and nine in fish and water, with total mean concentrations of 4 587.7 ng g-1, 1 098.5 ng g-1 and 34 ng ml-1 in sediment, fish tissues and water, respectively. Lower molecular weight PAHs were predominant, with naphthalene accounting for the highest concentration in all samples. Carcinogenic PAHs detected included benzo(a)pyrene, benzo(a)anthracene and chrysene. The predominance of lower molecular weight PAHs in the study area is an indication of recent pollution of petrogenic origin from the Warri Refining and Petrochemical Company’s refinery.